Production of plant protein from seeds and cake of industrial hemp: Overview of processing methods for food industry - D. I. Aleksanochkin; I. A. Fomenko; E. A. Alekseeva; I. M. Chernukha; N. G. Mashentseva (Пищевые системы)
Industrial hemp (Cannabis sativa L.) is a multifunctional raw material with a wide spectrum of applications. A huge interest in hemp has arisen in the food industry comparatively recently. Seeds and cake of hemp have the high protein content (20.00-38.70% and 27.90-40.70%, respectively), which makes them a promising raw material for production of concentrates, isolates, and hydrolysates for the food industry. Hemp cake is distinguished by the high content of fiber (17.41-60.38%) and can be used as a prebiotic component of food. In terms of the amino acid content, the amino acid composition of hemp exceeds the corresponding indicators of the reference protein recommended by WHO. The content of lysine is the only indicator, in which hemp protein is inferior to the “ideal” protein. Digestibility of protein of hulled hemp seeds is in a range from 90.8% to 97.5%, which is comparable to digestibility of casein. Digestibility of hemp isolate is 88-91%, which is 21.9% higher than that of soy protein isolate. Peptides and amino acids contained in hydrolysates of hemp protein can show the high biological activity. Hydrolysates attract interest among researchers not only because of their bioactivity but also because of their high digestibility and nutritional value. Targeted proteolysis is a tool that facilitates an improvement in the functional-technological properties of protein. Seeds and cake are a promising raw material for using in food technologies to produce vegetable oil, dietary fiber, protein preparations and functional products. The aim of this paper is to analyze the main methods for industrial hemp processing and promising directions of using protein products from waste of hemp oil production in the food industry.